Relative Infestation Intensity of Bamboo Leaf Roller, Algedonia coclesalis on Different Bamboo Species in Ranchi Region - Kumar, Arvind; Chandra, Girish; Singh, K. P. (Indian Forester, 2021)
Bamboo leaf roller Algedonia coclesalis is a noxious pest of bamboo species in India. In this paper the infestation level of Algedonia coclesalis on 17 different bamboo species has been studied for four years in Ranchi, Jharkhand, India. It has been resulted that A. coclesalis infestation initiates in the month of July and remains till October. Tree clustering result categorised all the bamboo species into three different relative susceptibility groups in which D. strictus, B. nutans and B. vulgaris were found to be the most threatened and susceptible species to bamboo leaf roller A. coclesalis in the region.